2017
DOI: 10.1038/modpathol.2017.93
|View full text |Cite
|
Sign up to set email alerts
|

Increased MYC copy number is an independent prognostic factor in patients with diffuse large B-cell lymphoma

Abstract: Patients with double-hit or triple-hit lymphoma have a significantly worse prognosis compared to patients with diffuse large B-cell lymphoma without MYC rearrangement. However, the prognostic importance of extra copies of MYC, BCL2, or BCL6 has not been fully explored. We studied 663 patients with de novo diffuse large B-cell lymphoma in whom the status of MYC/8q24, BCL2/18q21, and BCL6/3q27 were assessed by fluorescence in situ hybridization. Cases of double or triple extra copy lymphoma were defined by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 33 publications
(65 reference statements)
6
35
0
Order By: Relevance
“…Translocations involving MYC are a hallmark of Burkitt lymphoma, but they can occur in 5%‐15% of DLBCL, conferring a poorer prognosis in DLBCL patients treated with R‐CHOP and CHOP‐like regimens . In multivariate Cox regression modeling, MYC rearrangement was predictive of inferior survival and provided prognostic information independent of IPI score or stage for both OS and EFS . In a recent report from the Lunenburg Lymphoma Biomarker Consortium, MYC ‐R was associated with a significantly shorter PFS and OS, with a strong time‐dependent effect within the first 24 months after diagnosis; interestingly, the adverse prognostic impact of MYC ‐R in that study was only evident in patients with a concurrent rearrangement of BCL2 and/or BCL6 and an IG partner.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Translocations involving MYC are a hallmark of Burkitt lymphoma, but they can occur in 5%‐15% of DLBCL, conferring a poorer prognosis in DLBCL patients treated with R‐CHOP and CHOP‐like regimens . In multivariate Cox regression modeling, MYC rearrangement was predictive of inferior survival and provided prognostic information independent of IPI score or stage for both OS and EFS . In a recent report from the Lunenburg Lymphoma Biomarker Consortium, MYC ‐R was associated with a significantly shorter PFS and OS, with a strong time‐dependent effect within the first 24 months after diagnosis; interestingly, the adverse prognostic impact of MYC ‐R in that study was only evident in patients with a concurrent rearrangement of BCL2 and/or BCL6 and an IG partner.…”
Section: Discussionmentioning
confidence: 97%
“…5,23,[25][26][27][28][29][30][31] In multivariate Cox regression modeling, MYC rearrangement was predictive of inferior survival and provided prognostic information independent of IPI score or stage for both OS and EFS. 26,32 In a recent report from the Lunenburg Lymphoma Biomarker Consortium, 33 with t(14;18) had a significantly worse survival compared with those without the translocation. 37 A recent study showed that isolated BCL2 translocation was not predictive of outcome in the DLBCL patients as a whole, but did predict outcome in those with GCB type: Therefore, MYC/BCL2 DE is much more common than DHL.…”
Section: Discussionmentioning
confidence: 99%
“…MYC overexpression due to genetic aberrancies (e.g., translocation and amplification) can be used as a prognostic biomarker for certain B cell NHL subtypes. Based on a recent report, MYC amplifications or rearrangements can independently predict overall survival in patients of DLBCL (Quesada et al, 2017). Application of next-generation sequencing (NGS)-based technologies such as whole exome sequencing revealed the genomic mutational landscape of different types of B cell lymphomas.…”
Section: Diagnostic Prognostic and Therapeutic Implications Of Genementioning
confidence: 99%
“…Unique genetic changes, especially mutations such as GNA13 and EZH2 in GCB and MYD88, CARD11, and CD79B in ABC are found, respectively [6,7]. Chromosomal translocations in DLBCL involving regions with BCL6 (3q27), BCL2 [t(14;18) (q32;q21.3)], and MYC (single hit) comprise, respectively, approximately 30% (with predominance in ABC subtype), 20-30% (more commonly in GCB subtype), and 8-14% (similar distribution among ABC and GCB subtype) [8,9,10,11,12,13,14,15,16,17,18]. It is estimated that approximately 50% of DLBCL with MYC translocation demonstrate BCL2 and/or BCL6 rearrangement and that cases should be transferred to the high-grade B-cell lymphoma category [1,19,20].…”
Section: Diffuse Large B-cell Lymphoma Not Otherwise Specifiedmentioning
confidence: 99%